The Idea of Implementing a Deferred Prosecution Agreement with the Anti-Bribery Management System in Corruption Crime Management by Corporations in Indonesia - Zenno Januarsyah, Mas Putra; Pantja Astawa, I Gde; Atmasasmita, Romli; Gultom, Elisatris (International Journal of Criminology and Sociology, 2022)
Corporations are entities that have a large role in society, there are many positive roles to life, but not a few negative existences of activities that arise, including corruption. The purpose of this article is to analyze the implementation of the Deferred Prosecution Agreement (DPA) with the Anti-Bribery Management System (ABMS) in dealing with Corruption by Corporations in Indonesia. The method used in this article is normative juridical legal research. This article concludes ways to eradicate corrupt acts carried out remarkably, in turn experiencing obstacles in terms of the functioning of criminal law, even it can be said to be counter-productive. This is a concrete step towards the idea of implementing DPA as a restorative approach in the context of tackling corruption acts committed by corporations. By using the Anti-Bribery Management System (ABMS), it is expected that corrective steps will be obtained from the corporation.